The relationship between fear of COVID-19 and intention to get vaccinated. The serial mediation roles of existential anxiety and conspiracy beliefs. (January 2022) - Scrima, Fabrizio; Miceli, Silvana; Caci, Barbara; Cardaci, Maurizio
Abstract: Today, we witness the progress toward global COVID-19 vaccinations organized by countries worldwide. Experts say a mass vaccination plan is the only effective antidote against the spread of SARS-COV-2. However, a part of the world population refuses vaccination. The present study aimed to understand the impact of some individual variables on the intention to get vaccinated. Through a serial mediation model, we tested the influence of fear of COVID-19 on the intention to get vaccinated and the serial mediating effect of existential anxiety and conspiracy beliefs. Via a cross-sectional design this research was conducted with the participation of 223 French adults (Female: 69.5%; Male: 30.5%; M age = 30.26, SD = 13.24; range: 18–75 years) who responded to an online survey. The results showed a positive relationship between fear of COVID-19 and intention to get vaccinated; however, when this fear was associated with high levels of existential anxiety through conspiracy beliefs, the intention to get vaccinated decreased. Our findings were in line with Terror Management Health Model, which states that, in facing health threats, humans may strive to reduce their own perceived vulnerability not only by engaging in healthy behaviors but also denying or avoiding death anxiety, as anti-vaxxers do. Highlights: As a proximal defense, fear of COVID-19 increases intention to get vaccinated. Fear of COVID-19 increases existential anxiety. Existential anxiety increases conspiracy beliefs. Conspiracy beliefs increase intention to get vaccinated. Existential anxiety and conspiracy beliefs mediate the relation between fear of COVID-19 and intention to get vaccinated.